Implementation of Islamic Education Learning with Social Care Participants Educated - Imam Tabroni; Adisa Riski Bumi (Jurnal Multidisiplin Madani, 2022)
Social care, assumes that humans are social creatures who always live together, interact, collaborate, and have other human needs. Therefore, contradictory social acceptance of the problems facing society, to advance the role of science and technology, and also work cooperatively, collaboratively, and find solutions to build a better society. In a state that is able to prepare students in developing their basic potential as individuals and social beings and ready to accept all changes through PAI learning in the future. The process of implementing social Islamic learning can provide learning that causes life problems faced by students and the community. Therefore, the practical education of students depends on the interests and needs of the ummah through learning Islamic education.